PRESTASI BELAJAR MATEMATIKA DITINJAU DARI SIKAP SISWA TERHADAP MATA PELAJARAN MATEMATIKA - Richanatus Syarifah & Muslimah Zahro Romas (LPPM Universitas Proklamasi 45, 2017)
Having positive atitude on a difficult subject was a tough basic on having a good academicachievement. Although this was really a classic issue, however, this research was interesting.This research was conducted in a rural areas. Hypothetically, students would have goodmathematic achievement when they had posititve attitude on that subject. Forty two villageelementary students, grade fourth and fifth, participated in this research. Students’ attitudedata were collected through the attitude scale and the range of validity value was .318-.670.The students’ achievement in math was collected through their report cards. This researchrevealed that there was no correlation between students’ attitude on math and their mathachievement, rho = .037, p = .818. Reason of this research finding might be from students’life style. They were student villagers, and villagers usually were reluctant to express their realattitude. They might be unhappy with the teacher’s method in teaching math, however, theywere reluctant to deal with the teacher. Other reasons were also discussed.Keywords: Mathematic, attitude, achievement.